2009
DOI: 10.1039/b812724g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and phase behaviour of β-octaalkyl porphyrins

Abstract: A homologous series of three octakis-alkyl-substituted porphyrin (OAP) derivatives with alkyl chain lengths of C 8 , C 10 and C 12 has been synthesised. For each compound, both the free-base (i.e. two H-atoms) and the fourfold coordinated zinc complex were investigated, where the latter for each chainlength was found to exhibit liquid crystalline mesophase behaviour. At low temperatures 10 all three metal coordinated compounds formed a solid S phase with a structure based on a square packing of columns with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Compared with traditional disk molecules, dendrimer 1 with a C2-symmetry having a columnar LC phase on cooling, is unusual. To exhibit columnar mesophases, the traditional C2-symmetry molecules may consist of a macrocyclic core [ 56 , 57 ]. Introducing a chiral core to result in helical stacking columns by modulating the intermolecular π–π interaction between molecules is another approach [ 58 ].…”
Section: Formation Of Triazine-based Lc Dendrimers By Manipulating Their Molecular Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with traditional disk molecules, dendrimer 1 with a C2-symmetry having a columnar LC phase on cooling, is unusual. To exhibit columnar mesophases, the traditional C2-symmetry molecules may consist of a macrocyclic core [ 56 , 57 ]. Introducing a chiral core to result in helical stacking columns by modulating the intermolecular π–π interaction between molecules is another approach [ 58 ].…”
Section: Formation Of Triazine-based Lc Dendrimers By Manipulating Their Molecular Morphologymentioning
confidence: 99%
“…Co simulations for the conformations of dendrimers 1 and 2 showed that the steric eff the peripheral skeleton of 1 is more significant than that of 2 [54], i.e., the dendr formation of 1 is less coplanar due to congestion between the branched mainfram reducing the face-to-face π-π interactions between dendritic molecules and form columnar phase on thermal treatment. Compared with traditional disk molecu drimer 1 with a C2-symmetry having a columnar LC phase on cooling, is unusua hibit columnar mesophases, the traditional C2-symmetry molecules may consist o rocyclic core [56,57]. Introducing a chiral core to result in helical stacking colu modulating the intermolecular π-π interaction between molecules is another a [58].…”
Section: Lc Dendrimers With C2 Symmetrymentioning
confidence: 99%
“…For discotic LC molecules, the major driving force to enable columnar structures via self-assembly is mostly given by the peripheral modification of disc-shaped cores with long paraffinic chains, [4][5][6][7] where rigid p-systems and flexible side chains are segregated in a nanoscopic scale. Nevertheless, the volume balance between a discotic core and peripheral chains has a remarkable impact on the stable phase structures, 8 leading to the formation of other phases such as micelle cubic, [9][10][11] bicontinuous cubic, [12][13][14] crystalline, 15,16 and amorphous phases. 17,18 Therefore, in order to obtain columnar LC materials, the try-and-error in the synthesis process is required for every discotic p-system such as changing the number and length of chains.…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] The most significant LC behaviour was found by peripheral modification of octa-substituted and meso-tetraphenylporphyrinic derivatives. [2,[20][21][22][23][24][25][26][27][28] Additionally,s ome tetrapyrrolic macrocyclesp eripherally substituted have LCs properties and exhibit columnar mesophases. [29,30] Following our research interests in discotic LC and luminescent materials, [31][32][33] and considering the potential of functionalised meso-tetraarylporphyrins in this field, [34] we decided to prepareaseries of easily accessible porphyrins containing four (3a,b)o re ight (3c,d)a liphatic amide chains with different lengths.…”
Section: Introductionmentioning
confidence: 99%
“…on mesogenic porphyrins, many other scientific groups synthesised new porphyrinic derivatives and investigated their mesomorphic properties . The most significant LC behaviour was found by peripheral modification of octa‐substituted and meso ‐tetraphenylporphyrinic derivatives . Additionally, some tetrapyrrolic macrocycles peripherally substituted have LCs properties and exhibit columnar mesophases …”
Section: Introductionmentioning
confidence: 99%